Financial Distress: Earnings Management and Tax Aggressiveness Practices on Audit Report Lag - Tanril, Franky; Trisnawati, Estralita (E-Jurnal Akuntansi; Vol 35 No 5 (2025)DO - 10.24843/EJA.2025.v35.i05.p03, 2025)
Despite the existence of regulatory frameworks intended to ensure timely financial reporting, delays in the submission of audited financial statements remain prevalent. Audit Report Lag (ARL) continues to be a critical factor influencing the timeliness of financial disclosures. This study addresses a gap in the literature by providing empirical evidence on the influences of earnings management and tax aggressiveness on ARL, while also examining the moderating role of financial distress. The analysis focuses on companies within the cyclical and non-cyclical consumer sectors listed on the Indonesia Stock Exchange (IDX) over the period 2019 to 2023. Employing a moderated regression analysis using panel data, the study utilizes purposive sampling to identify 294 companies, yielding a total of 141 companies with 705 firm-year observations. The findings reveal that accrual-based earnings management is positively influence ARL. In contrast, tax aggressiveness is found to reduce ARL. Furthermore, financial distress attenuates the positive influence of earnings management on ARL, but it does not significantly alter the influence of tax aggressiveness on ARL. Keywords: Audit Report Lag; Earnings Management; Tax Aggressiveness; Financial Distress; ARL